Backward- and Forward-Looking Potential of Anaphors - Schumacher, Petra B.; Backhaus, Jana; Dangl, Manuel (Frontiers in Psychology, 2015)
Personal pronouns and demonstratives contribute differently to the encoding of information in the mental model and they serve distinct backward- and forward-looking functions. While (unstressed) personal pronouns are the default means to indicate coreference with the most prominent discourse entity (backward-looking function) and typically mark the maintenance of the current topic, demonstratives are used to refer to a less prominent entity and serve the additional forward-looking function of signaling a possible topic shift. In Experiment 1, we present an ERP study that examines the time course of processing personal and d-pronouns in German (er vs. der) and assesses the impact of two prominence features of the antecedent, thematic role and sentential position, as well as neurophysiological correlates of backward- and forward-looking functions of referential expressions. We tested the comprehension of personal and d-pronouns following context sentences containing two potential antecedents. In addition to the factor pronoun type (er vs. der), we varied the verb type (active accusative verbs vs. dative experiencer verbs) and the thematic role order (canonical vs. non-canonical) in the context sentences to vary the antecedent’s prominence. Time-locked to pronoun-onset, the ERPs revealed a general biphasic N400-Late Positivity for d-pronouns over personal pronouns with further subtle interactions of the prominence-lending cues in the early time window. The findings indicate that the calculation of the referential candidates’ prominence (backward-looking function) is guided by thematic role and positional information. Thematic role information, in combination with initial position, thus represents a central predictor during referential processing. Coreference with a less prominent entity (assumed for d-pronouns) results in processing costs (N400). The additional topic shift signaled by d-pronouns (forward-looking function) results in attentional reorienting (Late Positivity). This is further supported by Experiment 2, a story continuation study, which showed that personal pronouns trigger topic maintenance, while d-pronouns yield topic shifts.